(x-4y-9)dx+(4x+y-2)
Let us solve the differential equation "(x-4y-9)dx+(4x+y-2)dy=0."
Firstly, consider the system "\\begin{cases}x-4y-9=0 \\\\ 4x+y-2=0\\end{cases}" which is equivalent to "\\begin{cases}x-4y-9=0 \\\\ 16x+4y-8=0\\end{cases}" and to "\\begin{cases}x-4y-9=0 \\\\ 17x-17=0\\end{cases}." It follows that "\\begin{cases} x=1 \\\\ y=-2\\end{cases}."
Let us use the transformation "x=u+1,\\ y=v-2." Then we get "(u-4v)du+(4u+v)dv=0."
Also let "u=tv," and hence "du=tdv+vdt." It follows that "(tv-4v)(tdv+vdt)+(4tv+v)dv=0."
Since for "v=0" we have that "y=-2" is not a solution of the differential equation, let us divide both sides by "v:" "(t-4)(tdv+vdt)+(4t+1)dv=0." The last equation is equivalent to "(t^2-4t)dv+(t-4)vdt+(4t+1)dv=0," and hence to "(t^2+1)dv=-(t-4)vdt."
It follows that "-\\frac{dv}{v}=\\frac{(t-4)dt}{t^2+1}," and consequently "-\\int\\frac{dv}{v}=\\int\\frac{(t-4)dt}{t^2+1}." We get that "-\\ln|v|=\\frac{1}{2}\\int\\frac{2tdt}{t^2+1}-4\\int\\frac{dt}{t^2+1}=\\frac{1}{2}\\ln(t^2+1)-4\\arctan t+\\ln |C|," and hence
"8\\arctan t=\\ln(t^2+1)+2\\ln|v|+\\ln |C_1|=\\ln|(t^2+1)v^2C_1|."
It follows that "(t^2+1)v^2C_1=e^{8\\arctan t}."
Since "t=\\frac{u}{v}=\\frac{x-1}{y+2}" and "v=y+2," we have that
"((\\frac{x-1}{y+2})^2+1)(y+2)^2C_1=e^{8\\arctan \\frac{x-1}{y+2}}."
We conclude that the general solution is the following:
"((x-1)^2+(y+2)^2)C_1=e^{8\\arctan \\frac{x-1}{y+2}}."
Comments
Leave a comment